Enhanced catalysis of the electrochemical hydrogen evolution reaction using composites of molybdenum-based compounds, gold nanoparticles and carbon. Issue 31 (18th July 2016) - Joshi, Ubisha; Lee, Jing; Giordano, Cristina; Malkhandi, Souradip; Yeo, Boon Siang
Abstract : Molybdenum-based compounds and gold nanoparticles, in the presence of carbon (BP-2000), interacted synergistically to enhance the electrochemical hydrogen evolution reaction. Abstract : Molybdenum nitride has been recently reported to interact synergistically with gold to show an enhanced activity for the electrochemical hydrogen evolution reaction (2H + + 2e − → H2, HER). In this work, we elucidated the roles of nitrogen, carbon, molybdenum and gold on this observed phenomenon. Composites of Mo-based compounds, carbon black (black pearl 2000) and/or Au nanoparticles (AuNP ) were prepared, and their activities for the HER in a 0.5 M H2 SO4 electrolyte were measured using linear sweep voltammetry. We show and discuss here for the first time that, while the presence of carbon is necessary for the synergy phenomenon, the nitrogen atoms present in the compounds play no apparent role in this synergy. In fact, all the compounds containing Mo, namely Mo2 N, MoB and metallic Mo 0, exhibited extensive synergy with Au for the HER. A hypothesis for the enhanced catalysis of H2 evolution by the mixed metal composites is proposed and discussed.